PERUBAHAN MUSIK TRADISI GORONTALO: GAMBUS DAN POLOPALO MENJADI TIPOTUMBA - Mimy Astuty Pulukadang (Pascasarjana Institut Seni Indonesia Surakarta, 2009)
Tradition art as medium to get society’s expression had experienced a lot of change according to support the creativity of society. Based on creativity on tradition art force this has humanitarianism point in supporting society’s life. It supported tradition form medley. Tradition music usually was engaged region, society appetite, trust, tradition and style. Archipelago music history notes to mark sense changing appetite and because of function politics social change. Changing it most verily constitute influence of artistry the world and education knowledge. Its attending is that phenomena, bearing idea Gorontalo’s artist to give aesthetic touch to its tradition music because archipelago music diversity can’t divorce from artists creative job it. Gorontalo’s artist tries to poor idea to merge music Gambus is traditional and Polopalo as Tipotumba without leave traditional methods. Changed process that covers to form, function, and music meaning Tipotumba looked on can represent kawula’s distortion young of extern culture that progressively on familiar term with their life. This research utilize fenomenologi’s approaching because is seen according to study object, concerning with happening phenomenon on Gorontalo’s society. Downloading to look for a variety source which is lionized deep observational covers studi is library, observation, and interview.Music Tipotumba be not simply realization of creativity one eye but as an estetik’s opus artists that region music Gorontalo cans also be Gorontalo’s society icon at winks national and also international.Keywords: changing, Gambus and Polopalo, Tipotumba